Les épidémiologistes, les chercheurs en sciences sociales et l’organisation de la recherche médicale sur le sida en Afrique [1991] - Randall M. Packard; Paul Epstein (Genre, Sexualité et Société)
The development of medical research on AIDS in Africa resembles earlier efforts to understand the epidemiology of TB and syphilis in Africa. In all three cases early research focused on why these diseases exhibited different epidemiological patterns in Africa than in the west. Early explanations of these differences focused on the peculiarities of African behavior, while largely excluding from vision a range of environmental factors. These parallels provide a framework for examining how western ideas about AIDS in Africa developed, the role of social scientists in the formation of these ideas, and how these initial perceptions shaped the subsequent development of AIDS research, encouraging a premature narrowing of research questions. The paper warns that, as in the histories of TB and syphilis research, this early closure may generate inadequate and inappropriate responses to the African AIDS epidemic and limit our understanding of the disease.